2020
DOI: 10.1002/admi.202000450
|View full text |Cite
|
Sign up to set email alerts
|

The Electronic Conductivity of Single Crystalline Ga‐Stabilized Cubic Li7La3Zr2O12: A Technologically Relevant Parameter for All‐Solid‐State Batteries

Abstract: The next‐generation of all‐solid‐state lithium batteries need ceramic electrolytes with very high ionic conductivities. At the same time a negligible electronic conductivity σeon is required to eliminate self‐discharge in such systems. A non‐negligible electronic conductivity may also promote the unintentional formation of Li dendrites, being currently one of the key issues hindering the development of long‐lasting all‐solid‐state batteries. This interplay is suggested recently for garnet‐type Li7La3Zr2O12 (LL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 65 publications
4
32
0
Order By: Relevance
“…13 Dendrites were not observed in the case of LiPON, 13 with s e values (10 15 -10 12 S/cm) at least four orders of magnitude lower than those in LLZO and Li 3 PS 4 . In striking contrast, recently, Philipp et al 14 reported s e of ⇠10 10 S/cm at 293 K in single-crystal Ga-doped LLZO, and claimed that such "low" s e cannot be responsible for Li dendrite growth in LLZO. These evidences point to a lack of consensus on the effects of s e in SEs.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…13 Dendrites were not observed in the case of LiPON, 13 with s e values (10 15 -10 12 S/cm) at least four orders of magnitude lower than those in LLZO and Li 3 PS 4 . In striking contrast, recently, Philipp et al 14 reported s e of ⇠10 10 S/cm at 293 K in single-crystal Ga-doped LLZO, and claimed that such "low" s e cannot be responsible for Li dendrite growth in LLZO. These evidences point to a lack of consensus on the effects of s e in SEs.…”
Section: Introductionmentioning
confidence: 89%
“…It has been demonstrated that electrolyte decomposition products at both high and low voltages (vs. Li/Li + ) may display intrinsic electronic conductivity, 32,33,38,46 whose magnitudes remain elusive. 13,14,45 While s e values are typically reported for completeness, the focus of many reports (e.g., references in Figure 1) shifts entirely to the high intrinsic Li + -ionic conductivity of novel SE chemistries. Solid electrolytes that are oxides, sulfides, or selenides, and even phosphates and silicates, 25 typically display band gaps >4 eV as seen in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the electronic conductivity of some inorganic ceramic SEs has been shown to increase rapidly under high voltage. 21,22 Work with density functional theory has shown that enhanced electronic conductivity can originate from point defects 23 and internal pores and crack surfaces in the SE. 24 To systematically study the electronic conductivity-driven metal propagation in the SE, one must consider the SE as a mixed ionic-electronic conductor (MIEC).…”
Section: Progress and Potentialmentioning
confidence: 99%
“…This result is consistent with recent experimental data that gave a much lower electronic conductivity for single-crystal samples of LLZO than previously reported for polycrystalline samples. 55 Our analysis presented here exclusively considers bulk defect populations and their response to doping, and therefore we cannot exclude the possibility that other sources of free charge-carriers might facilitate direct inplace reduction of lithium ions to lithium metal. Previous theoretical work has observed dramatic band-gap reductions at the surfaces of LLZO (E bulk g = 5.46 eV, E surface g = 2.19 eV).…”
Section: Summary and Discussionmentioning
confidence: 99%